1970
DOI: 10.1137/0707045
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Stage Algorithm for Real Polynomials Using Quadratic Iteration

Abstract: We introduce a new three-stage process for calculating the zeros of a polynomial with real coefficients. The algorithm finds either a linear or quadratic factor, working completely in real arithmetic. In the third stage the algorithm uses one of two variable-shift iterations corresponding to the linear or quadratic case. The iteration for a linear factor is a real arithmetic version of the third stage of the algorithm for complex polynomials which we studied in an earlier paper. A new variable-shift iteration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(48 citation statements)
references
References 6 publications
(5 reference statements)
0
48
0
Order By: Relevance
“…+ h k q k : (8) The new estimate x (k+1) is determined such that it is the one root ofP (x) closer to x (k) . An example is given in Fig.…”
Section: Muller's Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…+ h k q k : (8) The new estimate x (k+1) is determined such that it is the one root ofP (x) closer to x (k) . An example is given in Fig.…”
Section: Muller's Methodsmentioning
confidence: 99%
“…(2){(7). This is followed by the iteration equation (8). We have observed that values q k computed according to Eq.…”
Section: Muller's Methodsmentioning
confidence: 99%
“…Therefore, the zeros are determined in increasing order, which usually keeps the deflation stable (see Wilkinson [8], Jenkins and Traub [9]). An iteration was terminated if monotonicity was violated.…”
Section: Shift Algorithmmentioning
confidence: 99%
“…The one modification that might be considered is that of applying the Jenkins-Traub method and its dual alternately, thus locating, in turn, a relatively small and then a relatively large zero. This would help towards alleviating the problem of deflation instability referred to by Jenkins and Traub [4]. Of course, this modification may also be considered as the Jenkins-Traub method applied to P, say, to produce a zero pt, and then the same method applied to the inverse polynomial ofPj(z) = P(z)/(z -Pj).…”
Section: =1mentioning
confidence: 99%